The CYGNO experiment, a directional detector for direct Dark Matter searches - Amaro, F. D. (2023)
The CYGNO project aims at the development of a high precision optical readout gaseous Tima Projection Chamber (TPC) for directional dark matter (DM) searches, to be hosted at Laboratori Nazionali del Gran Sasso (LNGS). CYGNO employs a He:CF$_4$ gas mixture at atmospheric pressure with a Gas Electron Multiplier (GEM) based amplification structure coupled to an optical readout comprised of sCMOS cameras and photomultiplier tubes (PMTs). This experimental setup allows to achieve 3D tracking and background rejection down to O(1) keV energy, to boost sensitivity to low WIMP masses. The characteristics of the optical readout approach in terms of the light yield will be illustrated along with the particle identification properties. The project timeline foresees, in the next 2-3 years, the realisation and installation of a 0.4 m$^3$ TPC in the underground laboratories at LNGS to act as a demonstrator. Finally, the studies of the expected DM sensitivities of the CYGNO demonstrator will be presented.